Analysis of Regional Economic Growth and Inflation in Indonesia1 - MB Nani Ariani; Ferry Hadyanto; Yayan Satyakti; Indra Yudha Mambea (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
This study aimed to analyze macroeconomic factors that affect economic growth and regional inflation. The data used in this study included macro data from 33 provinces in Indonesia from 2004 to 2014. We employed a panel regression with the general least square method to analyze the influence of government expenditure variables, credit, the number of workers and the Human Development Index on economic growth as our economic growth model. In addition, a regional inflation model was used to estimate factors that determined inflation by running a probit panel regression with marginal effects. In order to capture the determinant of dummy inflation, we included labor productivity and the highest contribution rank of regional inflation-contributing commodities to the probability of achieving the inflation target.